1998
DOI: 10.1001/archneur.55.3.395
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Cognitive Function and Onset of Dementia in Cognitively Healthy Elders

Abstract: Cognitively healthy elderly people maintain stable cognitive performance when measured longitudinally by both careful clinical evaluation and repeated psychometric testing. This stability is maintained unless and until they develop a dementing illness, at which time a sharp decline in performance is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
216
1
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(236 citation statements)
references
References 32 publications
13
216
1
6
Order By: Relevance
“…Numerous studies have now shown that subtle cognitive changes can precede the diagnosis of AD by a few years or more (Bäckman et al, 2001;Bondi et al, 1994Bondi et al, , 1995Bondi et al, , 1999Chen et al, 2001;Lange et al, 2002;Linn et al, 1995;Masur et al, 1994;Rubin et al, 1998;Small et al, 1998Small et al, , 2000Smith et al, 1998). As Sliwinski and colleagues (1996) have shown, the inclusion of such individuals with preclinical AD in a normative sample leads to an underestimate of the mean, an overestimate of the variance, and an overestimate of the effect of age on a given cognitive measure, all of which reduces the sensitivity of the measure for detecting mild impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have now shown that subtle cognitive changes can precede the diagnosis of AD by a few years or more (Bäckman et al, 2001;Bondi et al, 1994Bondi et al, , 1995Bondi et al, , 1999Chen et al, 2001;Lange et al, 2002;Linn et al, 1995;Masur et al, 1994;Rubin et al, 1998;Small et al, 1998Small et al, , 2000Smith et al, 1998). As Sliwinski and colleagues (1996) have shown, the inclusion of such individuals with preclinical AD in a normative sample leads to an underestimate of the mean, an overestimate of the variance, and an overestimate of the effect of age on a given cognitive measure, all of which reduces the sensitivity of the measure for detecting mild impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Although memory decline has been a focus (Elias et al, 2000;Grober et al, 2000;Kawas et al, 2003;Linn et al, 1995;Rubin et al, 1998), other domains of cognition also show rapid decline in comparison to those who do not develop AD . Defining the nature and timing of cognitive changes in AD is important for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…In most longitudinal studies, memory measures are better predictors of subsequent AD than executive function tests (Devanand et al, 1997;Elias et al, 2000;Linn et al, 1995;Masur et al, 1994;Rubin et al, 1998) though this point is somewhat controversial (Chen et al, 2001;Fabrigoule et al, 1998;Rapp & Reischies, 2005;Royall et al, 2004). In these prospective studies, cognitive scores at the time of a baseline assessment are used to predict the onset of dementia at future times.…”
Section: Introductionmentioning
confidence: 99%
“…Saúde Pública, Rio de Janeiro, 21(1):64-72, jan-fev, 2005 As mudanças cognitivas precoces relacionadas ao início de demência e as mudanças do envelhecimento normais foram acompanhadas por Rubin et al 3 . Os seus achados mostraram que pessoas idosas normais mantêm desempenho cognitivo estável quando medidos de forma longitudinal por avaliação clínica cuidadosa e testagem cognitiva repetida.…”
Section: Introductionunclassified